Transglutaminases: recent achievements and new sources - Martins, Ivone (2014)
Transglutaminases are a family of enzymes (EC 2.3.2.13), widely distributed in various organs, tissues, and body fluids, that catalyze the formation of a covalent bond between a free amine group and the γ-carboxamide group of protein or peptide-bound glutamine. Besides forming these bonds, that exhibit high resistance to proteolytic degradation, transglutaminases also form extensively cross-linked, generally insoluble, protein biopolymers that are indispensable for the organism to create barriers and stable structures. The extremely high cost of transglutaminase of animal origin has hampered its wider application and has initiated efforts to find an enzyme of microbial origin. Since the early 1990s, many microbial transglutaminase-producing strains have been found, and production processes have been optimized. This has resulted in a rapidly increasing number of applications of transglutaminase in the food sector. However, applications of microbial transglutaminase in other sectors have also been explored, but in a much lesser extent. Our group has identified a transglutaminase in the oomycete Phytophthora cinnamomi, which is able to induct defense responses and disease-like symptoms. In this mini-review, we report the achievements in this area in order to illustrate the importance and the versatility of transglutaminases.